2012
DOI: 10.3109/09537104.2012.658107
|View full text |Cite
|
Sign up to set email alerts
|

A myocardial ischemia- and reperfusion-induced injury is mediated by reactive oxygen species released from blood platelets

Abstract: In recent experimental studies, blood platelets have been found to exhibit some cardiodepressive effects in ischemic and reperfused guinea pig hearts independent of thrombus formation. These effects seemed to be mediated by reactive oxygen species (ROS). However, the source of these ROS - platelets or heart - remained still unknown. Isolated, buffer-perfused and pressure-volume work performing guinea pig hearts were exposed to a low-flow ischemia (1 ml/min) of 30 min duration and reperfused at a constant flow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…However, it has been also shown that in some circumstances, platelets may contribute to initiation and propagation of I/R myocardial injury ( Aiken et al, 1981 ; Vanhoutte and Houston, 1985 ; Yee et al, 1986 ; Patel et al, 2001 ; Seligmann et al, 2013 ). These apparently conflicting reports may reflect different experimental designs: platelets introduced into the coronary system of heart preparations not before but during or after ischemia, atherosclerotic coronary arteries or coronary endothelial barrier failure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has been also shown that in some circumstances, platelets may contribute to initiation and propagation of I/R myocardial injury ( Aiken et al, 1981 ; Vanhoutte and Houston, 1985 ; Yee et al, 1986 ; Patel et al, 2001 ; Seligmann et al, 2013 ). These apparently conflicting reports may reflect different experimental designs: platelets introduced into the coronary system of heart preparations not before but during or after ischemia, atherosclerotic coronary arteries or coronary endothelial barrier failure.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of correlation for healthy platelets suggests that a certain threshold of ROS should be reached to affect protective properties. Of note, a complete prevention of the post-ischemic cardio-depressive effects by platelets – administrated during ischemia or reperfusion on isolated guinea pig hearts – was observed after platelet pretreatment with the NADPH-oxidase inhibitor, DPI ( Seligmann et al, 2013 ). These data are in agreement with our data that ROS levels in hyperactive platelets are correlated to the extension of I/R injury and that platelet ROS derive, at least in part, from NADPH-oxidase.…”
Section: Discussionmentioning
confidence: 99%
“…This may reflect the inflammatory reaction of ischemia/reperfusion injury, which is in accordance with recent findings that platelets play a pathogenic role in this pathological process and are a therapeutic target and that their involvement determines the rate of complications in mice such as ventricular rupture. 6,36 Overall, the combined LIBS-MPIO/LGE imaging could provide important clinical information delineating the area at risk and inflammation, in addition to the area of necrosis as determined by LGE imaging. Whether the combination of these 2 imaging methods allows a clinically relevant risk prediction of adverse cardiovascular events in patients after MI remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Coapplication of the radical scavenger enzyme superoxide dismutase improved REHW during reperfusion indicating a role of ROS in the provoked IRI. Interestingly, by coapplication of the GPIIb/IIIa-blocker tirofiban the authors could show that the platelet-induced ROS-dependent myocardial dysfunction in their experimental model was independent of intracoronary platelet adhesion (49, 56, 66). In a follow up study, by applying a platelet pretreatment with diphenyliodonium chloride Seligmann et al elegantly proved that the shown cardiodepressive effects were mediated by ROS released from platelets and not the heart itself (49).…”
Section: Mediators Released By Plateletsmentioning
confidence: 99%